PENGEMBANGAN APLIKASI INFORMASI TA’LIM DENGAN LOCATION BASED SERVICE PADA PLATFORM ANDROID DI MASA PANDEMI COVID-19 - Mhammad Fadhil Fikri; Muhammad Yahya; Abdul Muis Mappalotteng (Program Studi S2 Pendidikan Teknologi dan Kejuruan, 2023)
The purposes of this study are to discover (1) the results of developing the location based service application on the Android platform that can be used to find ta'lim information during the Covid-19 pandemic, (2) the effectiveness of ta'lim information application using location based service on the Android platform during the Covid-19 pandemic, and (3) the practicality of ta'lim informationapplications using location based service during the Covid-19 pandemic. This type of study is Research and Development (R&D) using a prototype model. Data collection techniques used were literature studies, interviews, and questionnaires. The data analysis technique used was qualitative. The results of the study are: (1) the development of ta’lim location information application usinglocation based service on android platform during the Covid-19 pandemic is declared as valid andfeasible to be used measured by the media and content experts’ validation, then tested on functionality and maintainability aspects, (2) the test results of ta'lim information application using location basedservice on the android platform during the Covid-19 pandemic confirm that the application is effective to be used from the aspects of functionality, portability, reliability, and usability, as well as validation from the content expert, and (3) the test results of ta’lim information application using location based service on android platform during the Covid-19 is declared as practical to be used measured from the aspects of portability, security, and usability, as well as validation by the media expert.